Analysis Of Traditional Lopek Cik Ku Cake In Nagari Air Bangis - Maulani, Dira; Faridah, Anni; Gusnita, Wiwik; Andriani, Cici (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
This research was carried out as an effort to maintain the existence of the traditional Lopek Cik Ku cake among the current generation which will become literature (written books) and documentation in the future. The research was carried out in September-October 2023 in Nagari Air Bangis, West Pasaman Regency. The aim of this research is to identify the equipment, composition of ingredients, describe the technique, process of making Lopek Cik Ku, and the meaning of the traditional Lopek Cik Ku cake at special events or traditional events. The type of research used is qualitative research with a descriptive approach. Data information in this research was obtained from 8 informants including KUBE Warisan Umak, community women who are experts and have made Lopek Cik Ku in Nagari Air Bangis. The data collection techniques used were observation, interviews and documentation. Data analysis is carried out by reducing, presenting, concluding and verifying the data. The results of this research are that the ingredients for Lopek Cik Ku are white sticky rice, old grated coconut, brown sugar, water, salt and young leaves of klutuk banana. The tools used are, stove, frying pan, tray, steamer, strainer. The processing techniques are boiling, roasting and steaming. The method for processing Lopek Cik Ku is: The first step is to dry the banana leaves in the sun until they wilt, so that when wrapping they don't break, then roast the grated coconut and sticky rice separately until dry and brownish, grind the sticky rice, boil the brown sugar in water until dissolved and thick, then add it. roasted coconut and stir well, add the smooth sticky rice while stirring well, remove from heat and let cool, then wrap in banana leaves, then dry in the sun until dry to last longer.